Japanese Foreign Policy at the Crossroads : Challenges and Options for the Twenty-First Century. - Kawashima, Yukata (Brookings Institution Press, 2003)
The future of foreign policy in Japan is uncertain. The post-World War II paradigm that ensured security and prosperity for the Japanese people has lost much of its effectiveness. This book examines this uncertainty and explores the decision-making processes that have led Japan to this point.